(untitled) (Research, Society and Development, 2025)
Obesity is a multifactorial and chronic nutritional disease that is a growing condition in domestic cats, characterized by the excessive accumulation of body fat and is often associated with a series of comorbidities such as diabetes mellitus, dyslipidemia, and joint diseases, which compromise the health and well-being of animals. This article aims to show a narrative review of updated literature on feline obesity. The importance of this study lies in the need to promote a thorough assessment of the body state of felines, based on the analysis of the body mass index and the observation of clinical signs, such as motor difficulties and metabolic disorders. This careful evaluation is essential to identify factors predisposing to obesity, such as sedentary lifestyle, overeating, and hormonal disorders, including endocrine dysfunctions, such as hypothyroidism or Cushing’s syndrome, which can aggravate the condition. From a nutritional point of view, therapeutic intervention promotes gradual and safe weight loss, using hypocaloric and balanced diets that preserve muscle mass. The control of caloric intake, associated with a specific eating plan and frequent monitoring, is essential for the treatment’s success. The importance of this integrated approach, which combines clinical evaluation and personalized nutritional intervention, is to contribute to effectively controlling feline obesity, improving the quality of life of animals, and reducing the risks of associated comorbidities.